SISTEM PENGAJUAN JUDUL TUGAS AKHIR BERBASIS WEB DENGAN MODEL PENGEMBANGAN PROTOTYPE PADA PROGRAM STUDI TEKNIK INFORMATIKA UNIVERSITAS PAMULANG: SISTEM PENGAJUAN JUDUL TUGAS AKHIR BERBASIS WEB DENGAN MODEL PENGEMBANGAN PROTOTYPE PADA PROGRAM STUDI TEKNIK INFORMATIKA UNIVERSITAS PAMULANG - Octaviana Anugrah Ade Purnama (Journal of Research and Publication Innovation, 2023)
In undergraduate level higher education, completing the final assignment is one of the important requirements for students to get a bachelor's degree. The final assignment is a scientific work based on a research activity by students, and can be taken by students of the Informatics Engineering Study Program at Pamulang University starting in semester 7. The initial stage of completing the final assignment is that students must make a research title according to the topic to be taken. However, due to the absence of a system that monitors the title of the final assignment, it is not uncommon to find a title at the end of the Study Program that is not in accordance with the Study Program's field of research, namely Computer Science. For this reason, a system is needed that can be used by students and Study Programs in the process of submitting and approving the title of the final project. The expected system can also detect the same titles so as to minimize plagiarism. By using a prototype development model, this system has gone through practical tests in the field and evaluations to suit the needs expected by students and study programs. This system is also equipped with a title approval letter in the form of a .pdf file for students whose title submissions are accepted by the Study Program.